The Relationship of Emotional Intelligence and Stress In SMEs - Musa, Haslinda; Azmi, Fadlur Rahim; Abdullah, Abdul Rahim; Sedek, Muliati (IOSR-JBM, 2018)

(untitled)
Emotional intelligence is an important topic in management and entrepreneurial education. This study focused on the relationship between Emotional Intelligence (Cognition & Ability, Understanding Emotions, and Emotional Decision Making) and stress among SMEs. A total of 70 entrepreneurs from different areas in Melaka participated in the survey. Reliability analysis was applied to test the instrument’s reliability. Moreover, correlation analysis was applied to examine the relationship of EI factors with stress in SMEs. Regression analysis applied to determine the predicted factors of EI towards stress. The results of the analysis indicated cognition & ability, understanding other’s emotions and emotional decision making had a positive relationship with stress among SMEs. For the practicality of this study, emotional intelligence can be well implemented through education to instill a sound stress management to all potential entrepreneurs.